Masters of the Sabar: Wolof Griot Percussionists of Senegal. 2007. Patricia Tang. Philedelphia: Temple University press. xiv, 209 pp., 36 illustrations and transcriptions, glossary, bibliography, discography, index, CD (African Soundscapes Series). Gregory Barz, (series editor). - Tracey, Geoffrey (International Library of African Music, 2007)
pages: 120-122
Keywords: African Music; Senegal